Small Bowel Obstruction due to Intestinal Xanthomatosis - L. E. Barrera-Herrera; F. Arias; P. A. Rodríguez-Urrego; M. A. Palau-Lázaro (Hindawi Limited, 2015)
Vast majority of bowel obstruction is due to postoperative adhesions, malignancy, intestinal inflammatory disease, and hernias; however, knowledge of other uncommon causes is critical to establish a prompt treatment and decrease mortality. Xanthomatosis is produced by accumulation of cholesterol-rich foamy macrophages. Intestinal xanthomatosis is an uncommon nonneoplastic lesion that may cause small bowel obstruction and several cases have been reported in the English literature as obstruction in the jejunum. We report a case of small intestinal xanthomatosis occurring in a 51-year-old female who presented with one day of copious vomiting and intermittent abdominal pain. Radiologic images revealed jejunal loop thickening and inflammatory changes suggestive of foreign body obstruction, diagnostic laparoscopy found two strictures at the jejunum, and a pathologic examination confirmed a segmental small bowel xanthomatosis. This case illustrates that obstruction even without predisposing factors such as hyperlipidemia or lymphoproliferative disorders.